Electrochemical Transport in CuCl/HCl(aq) Electrolyzer Cells and Stack of the Cu–Cl Cycle. Issue 4 (26th February 2020) - Farsi, Aida; Zamfirescu, Calin; Dincer, Ibrahim; Naterer, Greg F.
Abstract : This paper develops a comprehensive predictive model for the CuCl/HCl(aq) electrolyzer stack in the electrochemical unit of the Cu–Cl cycle of hydrogen production. A strong aqueous anolyte is fed into the stack and forms complex speciation. The unit single cell is modeled to predict the decomposition voltage by applying the Gibbs energy minimization method (GEM). The kinetic correlations are incorporated to take into account the overpotential losses during the hydrogen generation process under a non-equilibrium condition with the stack under potential. To evaluate the single-cell contribution to the average performance of stack, a hydrodynamic analysis reveals the anolyte and catholyte flow distribution using a finite element method for solutions of the equation of mass and momentum conservation equations of the flow field. Using the simulated stack, the voltage spread across the individual cells in the stack, cell and stack voltage efficiency, and the sensitivity of stack performance under the operating conditions, are investigated. It is shown that the speciation model has good agreement with data in past literature. With an increase in the stack operating temperature from 25 °C to 65 °C, the average stack efficiency improves from 68% to 72%. Cells close to the anolyte or catholyte input ports possess a higher voltage efficiency than other cells. This is mainly due to less electrolyte received by the cells placed in the middle of the stack for the X-shape bipolar modules, resulting in less decomposition potential.